Harmoni dalam Keberagaman: Internalisasi Nilai Memenjor dan Ngelawar dalam Perayaan Natal sebagai Perekat Identitas Masyarakat Multikultur di Desa Blimbingsari, Jembrana - Dewa, Dewa Ketut Satria Anggita; Sujana, I Putu Windu Mertha; Budiarta, I Wayan (Ganesha Civic Education Journal, 2025)
This study aimed to explore the internalization of Balinese local cultural values through the Memenjor and Ngelawar traditions during the Christmas celebration among the Balinese Christian community. A qualitative descriptive ethnographic approach was employed to capture the social and cultural dynamics embodied in these practices. Data were collected through participant observation, in-depth interviews, and document analysis. The data were analyzed using the interactive model of Miles and Huberman, which involved data reduction, data display, and conclusion drawing with verification. Data validity was ensured through source triangulation and member checking. The findings reveal that the Memenjor and Ngelawar traditions serve not only as forms of cultural preservation but also as practical means of instilling Pancasila values, fostering unity, and strengthening cultural identity within a multicultural society. This study highlights the importance of integrating local cultural heritage into character and civic education and suggests further research on similar cultural integration practices in other diverse communities.